al-Qiyadah al-idariyah fi al-islam - Abu al-Fadl,'Abd al-Shafi Muhammad (al-Qahirah : al-Ma'had al-'Alami lil-Fikr al-Islam, 1996)
Review of contemporary concepts of administrative leadership coupled with an extrapolation of an Islamic model from classic & modern sources.
Includes bibliographical references (pages 343-354).
Keywords: Leadership -- Religious aspects -- Islam; Management -- Religious aspects -- Islam